Microplastics in Sea Turtles, Marine Mammals and Humans: A One Environmental Health Perspective - Meaza, Idoia; Toyoda, Jennifer H; Wise Sr, John Pierce (Frontiers in Environmental Science, 2021)
Microplastics are ubiquitous pollutants in the marine environment and a health concern. They are generated directly for commercial purposes or indirectly from the breakdown of larger plastics. Examining a toxicological profile for microplastics is a challenge due to their large variety of physico-chemical properties and toxicological behavior. In addition to their concentration, other parameters such as polymer type, size, shape and color are important to consider in their potential toxicity. Microplastics can adsorb pollutants such as polycyclic aromatic hydrocarbons (PAHs) or metals on their surface and are likely to contain plastic additives that add to their toxicity. The observations of microplastics in seafood increased concern for potential human exposure. Since literature considering microplastics in humans is scarce, using a One Environmental Health approach can help better inform about potential human exposures. Marine mammals and sea turtles are long-lived sentinel species regularly used for biomonitoring the health status of the ocean and share trophic chain and habitat with humans. This review considers the available research regarding microplastic and plastic fiber exposures in humans, marine mammals and turtles. Overall, across the literature, the concentration of microplastics, size, color, shape and polymer types found in GI tract and feces from sea turtles, marine mammals and humans are similar, showing that they might be exposed to the same microplastics profile. Additionally, even if ingestion is a major route of exposure due to contaminated food and water, dermal and inhalation studies in humans have provided data showing that these exposures are also health concerns and more effort on these routes of exposures is needed. In vitro studies looked at a variety of endpoints showing that microplastics can induce immune response, oxidative stress, cytotoxicity, alter membrane integrity and cause differential expression of genes. However, these studies only considered three polymer types and short-term exposures, whereas, due to physiological relevance, prolonged exposures might be more informative.